البطالة في العراق .. الواقع وتحديات المعالجة (المجلة العراقية للعلوم الاقتصادية, 2018)
Unemployment today is one of the problems that experienced by the most of human societies, albeit to varying degrees, particularly communities of the developing countries, including Arab countries. This problem worries about the decision-makers in those countries. In Iraq it was different than in many of the Arab countries during the sixties and early seventies. As Iraq was not suffering from clear unemployment, but this might require the use of Arab labor to fill shortages in the labor force in the seventies, as the number of expatriate Arab labor to work in Iraq more than three million workers, most of them were from Egypt. But the condition experienced by Iraq has led to a large imbalance in the labor market. The Iraqi economy is unable to absorb new labor entering the labor market, which has exacerbated the problem of the unemployed, to become the biggest social, economic problem facing the Iraqi society in its modern history, to reach a high levels hit in the year (2006) about (17.97%), of the total economically active population. The research suggested a number of techniques to treat the problem of unemployed in Iraq economy